Motivating Students Through Content and Curriculum Models: Building a Sport Education Tactical Games Model (SETGM) Unit on Spikeball. Issue 7 (15th September 2022) - Threatt, Ashley S.; Simonton, Kelly L.; Layne, Todd E.
Abstract: The purpose of this article was to reemphasize the importance of evidence-based instruction models, specifically the hybrid model called the Sport Education Tactical Games Model (SETGM). In addition to rehashing the importance of models-based approaches for student learning and motivation, we apply the approach by laying out the building blocks for creating a SETGM-focused lifetime games unit on the new and enticing content activity called, Spikeball, Given Spikeball's trend in the United States, its malleability for skill ability modifications, and limited technical culture makes this game ideal for student learning and enjoyment in PE. We begin with an overview the SETGM model and then provide practitioners the building blocks for creating a PE unit on Spikeball following the assumptions of the model.